Cytochromes P450: novel drug targets in the war against multidrug-resistant Mycobacterium tuberculosis. (1st June 2003) - Munro, A.W.; McLean, K.J.; Marshall, K.R.; Warman, A.J.; Lewis, G.; Roitel, O.; Sutcliffe, M.J.; Kemp, C.A.; Modi, S.; Scrutton, N.S.; Leys, D.
Abstract : Novel drug strategies are desperately needed to combat the global threat posed by multidrug-resistant strains of Mycobacterium tuberculosis (Mtb). The genome sequence of Mtb has revealed an unprecedented number of cytochrome P450 enzymes in a prokaryote, suggesting fundamental physiological roles for many of these enzymes. Several azole drugs (known inhibitors of cytochromes P450) have been shown to have potent anti-mycobacterial activity, and the most effective azoles have extremely tight binding constants for one of the Mtb P450s (CYP121). The structure of CYP121 has been determined at atomic resolution, revealing novel features of P450 structure, including mixed haem conformations and putative proton-relay pathways from protein surface to haem iron. The structure provides both a platform for investigation of structure/mechanism of cytochrome P450, and for design of inhibitor molecules as novel anti-tubercular agents.